Comparison of the Effectiveness of Ringer’s Lactate and 0.9% NaCl on Mortality in Adult Sepsis Patients: An Evidence-Based Case Report - Ridwan, Muhammad Rafif; Ridwan, Faras Khairunnisa; Ridwan, Muhammad Ijlal; Surianty Susilo (The Avicenna Medical Journal, 2025)
Background: The selection of crystalloid fluid in sepsis resuscitation affects acid-base balance, organ perfusion, and mortality. 0.9% NaCl (normal saline, NS) is the standard fluid, but its high chloride content has the potential to cause physiological disturbances. In contrast, balanced crystalloids such as Ringer's Lactate (RL) have an electrolyte composition closer to physiological plasma and are thought to provide better clinical outcomes. Recent evidence suggests a possible role for RL in reducing mortality in patients with sepsis, although some studies report mixed results. This study aims to evaluate the effectiveness of Ringer's Lactate compared to 0.9% NaCl on mortality in adult patients with sepsis, using an evidence-based case report approach to inform fluid resuscitation decisions. Methods: A literature search was conducted in October 2025 through PubMed NCBI, Medline EBSCO, ScienceDirect, and Google Scholar. Four studies met the inclusion criteria (3 RCTs, 1 SR/MA of RCTs) and were subsequently screened according to the Centre for Evidence-Based Medicine (CEBM) guidelines for critical appraisal, relative to validity, relevance, and practicality to the clinical scenario. Results: Across the included studies, the direction of effect generally favored RL over NS with respect to mortality outcomes. However, effect estimates were reported using different measures, including risk ratios and hazard ratios, and not all observed differences reached statistical significance. Given methodological heterogeneity and identified risks of bias, quantitative pooling of results was not performed, and findings were interpreted qualitatively. Conclusion: The use of Ringer’s Lactate in adult patients with sepsis appears to be associated with a favorable direction of effect on mortality compared with 0.9 NaCl. Nevertheless, the certainty of this evidence is limited, and definitive conclusions regarding superiority cannot be drawn. Keywords: NaCl, balanced crystalloid, normal saline, mortality, Ringer’s lactate, sepsis